Effects of water and fertilizer management on soil bacterial communities, enzyme activities, and nutrient availability in greenhouse tomatoes - Xiaona Lyu; Hasnuri Mat Hassan; Yaling Zan; Jiongrui Tan (PLoS ONE, 2025)
Irrigation and fertilization strategies have been extensively employed to enhance the growth and yield of greenhouse tomatoes. However, the impacts of divergent fertilizer application patterns on soil microbial communities under water-saving irrigation regimes in China’s arid and semi-arid zones remain underexplored. In this study, a pot experiment was conducted in the greenhouse of Yuncheng University, Shanxi Province, incorporating three irrigation levels (I1, 90%–100% field capacity [Fs]; I2, 72%–80% Fs; I3, 54%–60% Fs) and four fertilization modes (C1, soluble organic–inorganic fertilizer combination; C2, sole soluble inorganic fertilizer; C3, sheep manure–inorganic fertilizer combination; C4, sole soluble organic fertilizer) to evaluate the effects of water-fertilizer management on the growth and physiological attributes of greenhouse tomatoes. Results demonstrated that irrigation regimes and fertilization patterns significantly modulated bacterial richness and diversity, as quantified by amplicon sequence variants (ASVs). The C1 treatment (soluble organic–inorganic fertilizer integration) exhibited the highest bacterial alpha diversity (Shannon index: 7.29). In beta diversity analysis, it induced the most distinct community structures, particularly under I3 (PCo1 = 17.96%) where it strongly diverged from C3. Microbial communities under I2 (PCo1 = 11.13%) showed greater homogeneity while preserving treatment-specific patterns, suggesting slight deficit irrigation balances stability and functional differentiation. The C1 treatment also elicited the most pronounced enhancement in soil enzyme activities, particularly phosphatase (PHO, 9.51 mg g ⁻ ¹) and catalase (CAT, 2.29 mL g ⁻ ¹). Conversely, reduced irrigation (I3) corresponded with decreased bacterial diversity, whereas slight deficit irrigation (I2) sustained higher microbial abundance compared to severe deficit irrigation. Additionally, I2 elevated soil pH (8.04), available phosphorus (AP: 10.39 mg kg ⁻ ¹), and soil nitrate nitrogen (SNO₃ ⁻ -N: 5.02 mg kg ⁻ ¹). These findings provide critical insights into optimizing water-fertilizer strategies to enhance microbial activity and nutrient cycling in greenhouse tomato production systems. Phylogenetic analysis identified Actinobacteriota (26.06%), Proteobacteria (25.89%), Chloroflexi (12.42%), and Acidobacteriota (11.03%) as the dominant bacterial phyla. Significant positive correlations were observed between invertase, urease, catalase, and alkaline phosphatase activities and microbial diversity indices (ASVs, ACE, Chao1, Shannon index). This study advances our understanding of how rhizosphere bacterial communities adapted to fertilization regimes under water stress, offering novel perspectives for precision management of greenhouse agroecosystems in water-constrained regions.